Nano-biopesticides: Present concepts and future perspectives in integrated pest management - de Oliveira, Jhones Luiz [UNESP] (2020)
In this chapter, the potential of nanotechnology to improve the stability and effectiveness of biopesticides is addressed. Whether in the encapsulation of biomolecules extracted from plants, fungi, bacteria that have a prolonged action or also through the numerous biomaterials synthesized by biogenic processes, generating biocompatible and more efficient biopesticides. In addition to presenting an updated literature approach, it also brings future perspectives for these formulations in integrated pest management. Highlights the need a close and efficient collaboration between the different actors in society (universities, research centers, industrial companies, agricultural producers and government regulatory agencies) for fixation and growth of these biopesticide based in agricultural market.